Quantification of Crystalline Linagliptin Form-A in Amorphous 5 mg Tablets using Calibration curve Method by using Powder X-Ray Diffraction (PXRD) - Rao C V, Nageswara (International Journal of Pharmaceutical & Biological Archive, 2017)
The ability to detect and quantify polymorphism of pharmaceutical compounds is critically important in ensuring weather the formulated product delivers the desired therapeutic properties or not because different polymorphic forms of a drug exhibit different solubilities, stabilities and bio-availabilities. Amorphous materials are often preferred in the pharmaceutical industry due to their enhanced dissolution rate and bioavailability. Since the amorphous state is metastable and thermodynamically less stable relative to the crystalline state, there is always a potential for unexpected crystallization in storage. Conversion of amorphous to crystalline state can be evaluated by stability studies. Accurate quantification of crystalline phase present in drug materials has become increasingly imperative, due to stringent regulatory concerns about polymorph characterization. In the present study, a quantification PXRD method has been developed to determine the amount of Linagliptin Form-A in Linagliptin amorphous 5 mg tablets. This method is capable of determining the amount of Linagliptin Form-A in Linagliptin amorphous drug substance and Linagliptin tablets. This study emphasizes on the importance of mathematical calculation for physical mixture preparation for polymorphic quantification in drug product. Validation of quantization method was carried out with respect to specificity, precision, ruggedness, linearity, robustness, Limit of Detection (LOD) and Limit of Quantification (LOQ). This method can also be used at the manufacturing site to check the presence of crystalline phase of Linagliptin Form-A in amorphous drug substance and drug product.